2004
DOI: 10.1002/ccd.20213
|View full text |Cite
|
Sign up to set email alerts
|

Particle debris from a nanoporous stent coating obscures potential antiproliferative effects of tacrolimus-eluting stents in a porcine model of restenosis

Abstract: Polymer stent coatings may not be suitable for drug elution because of inherent proinflammatory effects. A previous study suggested a beneficial effect of a stent eluting tacrolimus from a nanoporous ceramic aluminum oxide coating in a rabbit restenosis model. We investigated whether this stent is effective in preventing in-stent restenosis in a porcine restenosis model. Thirty-four juvenile swine underwent balloon overstretch injury and were subjected to implantation of either stainless steel (bare) stents, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 26 publications
1
52
0
Order By: Relevance
“…Though the surface modification by ceramic coating did not show significant effect in reducing the neointima in a rabbit model, the release of tacrolimus reduced neointimal thickness in a dose dependent (52% and 56% reduction for 60 and 120 mg, respectively) manner [146]. Recently, it was reported that this kind of ceramic coating may liberate particle debris which in turn affects the antiproliferative effect of tacrolimus and results in a significant increase in the neointima as compared to the control uncoated stents [147].…”
Section: Porous Materialsmentioning
confidence: 94%
“…Though the surface modification by ceramic coating did not show significant effect in reducing the neointima in a rabbit model, the release of tacrolimus reduced neointimal thickness in a dose dependent (52% and 56% reduction for 60 and 120 mg, respectively) manner [146]. Recently, it was reported that this kind of ceramic coating may liberate particle debris which in turn affects the antiproliferative effect of tacrolimus and results in a significant increase in the neointima as compared to the control uncoated stents [147].…”
Section: Porous Materialsmentioning
confidence: 94%
“…Recent in vivo studies have demonstrated that the shedding of particle debris released from the nanoporous coatings produces a great increment of neointimal hyperplasia. 124 Fine et al reported that drug-releasing coronary stents based on Ti promote better interactions with ECs. 125 In this study, a new material called rosette nanotubes without drugs was coated on Ti stent surfaces, aiming to enhance the EC adhesion and proliferation.…”
Section: Cardiovascular Stentsmentioning
confidence: 99%
“…However, preclinical studies have shown variability regarding the effectiveness of stents coated with nanoporous materials. 34,35 Although biocompatibility has been documented, nanoparticle debris ejected from the stent surface has been observed. This debris could provoke inflammation and subsequent restenosis.…”
Section: Nanoporous and Nanostructured Surfacesmentioning
confidence: 99%